2018
DOI: 10.1126/scisignal.aaf3998
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of competitive cytokine signaling predicts tissue thresholds for the propagation of macrophage activation

Abstract: Toll-like receptor (TLR) signaling regulates macrophage activation and effector cytokine propagation in the constrained environment of a tissue. In macrophage populations, TLR4 stimulates the dose-dependent transcription of nuclear factor κB (NF-κB) target genes. However, using single-RNA counting, we found that individual cells exhibited a wide range (three orders of magnitude) of expression of the gene encoding the proinflammatory cytokine tumor necrosis factor-α (TNF-α). The TLR4-induced transcriptional res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
53
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 87 publications
(157 reference statements)
11
53
1
Order By: Relevance
“…Notably, only a single p65 translocation event (rather than repeated oscillation) was observed within the 3h data acquisition period of confocal imaging. This is similar to previous analyses of murine bone marrow-derived macrophages from transgenic mice in response to either Lipid A or LPS (9,10).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Notably, only a single p65 translocation event (rather than repeated oscillation) was observed within the 3h data acquisition period of confocal imaging. This is similar to previous analyses of murine bone marrow-derived macrophages from transgenic mice in response to either Lipid A or LPS (9,10).…”
Section: Discussionsupporting
confidence: 89%
“…NF-B transcriptional activity was monitored using a lentiviral construct (B-NLSluc) that expresses firefly luciferase under the control of the classical NF-B promoter (38). For imaging, the human p65 sequence was amplified from p65-dsRedXp (32) and C-terminally fused with AmCyan protein using a previously described lentiviral vector (9). Lentivirus production was carried out as per (39).…”
Section: Lentiviral Nf-b Transcriptional Activity Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the sensing step involves capturing extracellular IL-2, the feedback is confined to local regions and only some cells sense sufficient to IL-2 to proliferate 63 . Competitive cytokine uptake is involved in TNF paracrine signaling as well 64 . In the case of a synthetic genetic circuit implemented in yeast, with topological similarity to TNF intercellular feedback and that exhibited strong positive feedback and rapid degradation of the secreted cue, the proportions of cells in upper and lower modes of activation were found to depend on cell density 65 .…”
Section: Discussionmentioning
confidence: 99%
“…In general, we expect that the NF-κB system (or in fact the combined action of other systems, including MAP kinase (Rouse et al, 1994) or p53 tumour suppressor (Alexandrova and Marchenko, 2015)) in individual cell types might exhibit different sensitivities and recovery kinetics following temperature exposure. For example, we previously showed that TNFα stimulation in human osteosarcoma cells resulted in "all-or-nothing" NF-κB responses following HS (Kardynska et al, 2018), while tissue-level architecture might impose additional spatial constraints (Bagnall et al, 2018). We suggest that further efforts should combine dynamical modelling with cell fate, in order to better understand the relationship between temperature and NF-κB as well as cell proliferation and apoptosis in the more relevant cancer or inflammatory context.…”
Section: Discussionmentioning
confidence: 99%